Female ACL injury prevention with a functional integration exercise model - Pettineo, S. J.; Jestes, K.; Lehr, M. (Strength and Conditioning Journal, 2004)
A thorough review of the literature reveals that female athletes have a higher incidence of sustaining an anterior cruciate ligament (ACL) tear compared to their male counterparts. This article briefly describes the associated risk factors, anatomy, and etiology of the female ACL tear. More importantly, the primary objective of the article is to present a research driven functional training model designed to prevent ACL tears.